2013
DOI: 10.1097/qad.0b013e32835fd873
|View full text |Cite
|
Sign up to set email alerts
|

GPS-measured distance to clinic, but not self-reported transportation factors, are associated with missed HIV clinic visits in rural Uganda

Abstract: Objective Studies of the association between transportation barriers and HIV-related health outcomes have shown both positive and negative effects, possibly because a reliable, validated measure of transportation barriers has not been identified. Design Prospective cohort study of HIV-infected patients in rural Uganda. Methods Participants were enrolled from the HIV clinic at the regional referral hospital in Mbarara, Uganda as part of the Uganda AIDS Rural Treatment Outcomes (UARTO) Study. We collected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 33 publications
1
74
0
Order By: Relevance
“…33 Predictors of nonadherence in subSaharan Africa include higher pill burden (twice-daily regimens vs. once-daily regimens), 34 stavudine-containing regimens, 35 geographic or transportation-related barriers, 36 and Global Positioning System measured distance from home to clinic. 37 In multiple settings, younger age predicts virologic rebound, and clinicians and ART programs should more effectively address behavioral, structural, and psychosocial barriers to ART adherence and provide adherence support for younger HIV-infected persons initiating ART.…”
Section: Discussionmentioning
confidence: 99%
“…33 Predictors of nonadherence in subSaharan Africa include higher pill burden (twice-daily regimens vs. once-daily regimens), 34 stavudine-containing regimens, 35 geographic or transportation-related barriers, 36 and Global Positioning System measured distance from home to clinic. 37 In multiple settings, younger age predicts virologic rebound, and clinicians and ART programs should more effectively address behavioral, structural, and psychosocial barriers to ART adherence and provide adherence support for younger HIV-infected persons initiating ART.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, patients may not report travel times accurately, as shown in another study from a rural region of Uganda where travel time reported by patients attending an HIV clinic differed from the measured time of travel. 42 It is unknown whether these differences would persist if they were evaluated with more precise residential localization. Although we assigned travel speeds to various land surfaces based on values used in other studies, 10,27 they may not capture the actual travel times experienced by our patients.…”
Section: Discussionmentioning
confidence: 99%
“…This reorganization is justified primarily by the promising results reported in the literature for PLWHA who are monitored in a primary care setting [18] and by evidence that centralization of HIV/AIDS services and minimizing the distance between the homes of PLWHA and health facilities are factors that affect the likelihood that PLWHA will follow treatment protocols [19][20][21].…”
Section: Discussionmentioning
confidence: 99%